MODERN METHODS AND TOOLS FOR REGULATION OF PROJECT FINANCE RISKS - A. M. Harmath (Финансы: теория и практика, 2017)
This article presents the author’s own classification of risks for projects realized on the project finance principles. The classification is of particular relevance since most of the risks it highlights such as currency and interest rate risks, risks of commercial viability of the project including price risk and sales risk, along with project deadline overdue risks and cost overruns are beginning to plague investment projects implemented by many borrowers.In addition, the paper contains a thorough analysis of all the identified risk categories and describes state-of-theart methods and tools to mitigate the above risks. The author emphasizes the role of a qualified and experienced project team, licensed appraisers and external consultants, risk monitoring, and an adequately set-up contractual base as core elements of effective project risk management.